Immune-related adverse events are associated with therapeutic efficacy of immunotherapy in patients with melanoma brain metastases. Issue 1 (14th November 2022) - Huo, Cecilia W.; Gunadasa, Indika; Gkolia, Panagiota; Shackleton, Mark; Hunn, Martin
Abstract : Immunotherapy with T-cell checkpoint inhibitors have changed the treatment landscape for patients with melanoma brain metastases (MBMs), offering increased survival compared with historical outcomes. We sought to identify clinical features associated with intracranial tumour responses or progression-free survival (PFS) in patients with MBMs treated with immunotherapy. Patients with MBMs treated with immunotherapy from August 2013 to March 2020 were identified through local databases. Melanoma disease burdens and immune-related adverse events (irAEs) were assessed retrospectively by review of patient medical records. Efficacy was evaluated by determining objective response rates (ORRs) in brain metastases using immune-Response Evaluation Criteria in Solid Tumours criteria, MBM-specific survival and overall PFS. Twenty-six patients were identified as eligible for this study. The presence and volume of extracranial metastases (ECM) were associated with a non-significant trend of reduced intracranial ORRs and PFS. Patients with irAEs, on the other hand, had significantly increased intracranial ORRs and PFS compared to those without irAEs. Severe, grade ≥3 irAEs and co-occurrence of ≥2 irAEs were also significantly associated with longer PFS. The presence and volume of ECM correlated inversely with development and severity of irAEs. We report a strong association between the development of irAEs and favourable melanoma-specific outcomes in patients with MBMs receiving immunotherapy. Contrary to previous studies, we found that co-occurrence of ECM in these patients was associated with fewer irAEs and reduced treatment efficacy.